Homo-epitaxial growth of single crystal diamond in the purified environment by active O atoms. (September 2018) - Liu, Jinlong; Lin, Liangzhen; Zhao, Yun; Zheng, Yuting; An, Kang; Wei, Junjun; Chen, Liangxian; Hei, Lifu; Wang, Jingjing; Feng, Zhihong; Li, Chengming
Abstract: The pure oxygen was introduced into the growth environment of the single crystal diamond with different contents, and the growth characteristics of single crystal diamond and the reaction dynamics in the plasma were studied in detail. As the ratio of O2 to H2 is up to 1.5%, the unique shaped etching pits with eight symmetric crystallographic planes appear. Optical emission spectra present typical characteristic radicals in the O2 incorporated growth environment. With amount of O2 increases, the growth rate decreases gradually due to the low active carbon source concentration and electron temperature. In the carbon contained hydrogen plasma, O2 will react with CH radicals preferentially at low concentration and the dynamic equilibrium of CH and C2 radicals was achieved at the O2 concentration of 0.5% and 1%. Accompanying with the O2 addition, the nitrogen and silicon related impurities have been reduced during the epitaxial growth process. Meanwhile, all of the FWHM of characteristic peaks in Raman decrease obviously after the epitaxial growth without and with O2 addition, and FWHM of most samples are about 2.6 cm −1, which are comparable with the natural type IIa SCD without stress. Highlights: The epitaxial growth of high quality single crystal diamond in the purified environment was studied. The unique shaped etching pits with eight symmetric crystallographic planes were found. The reaction dynamics in the CH4 /H2 plasma with O2 incorporation was discussed using OES. The crystal quality of epitaxial diamond layer was improved by O2 addition.